The Strict Liability by Corporate in Enforcement of Environmental Law - Purnomo Wulandari; Sri Endah Wahyuningsih (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to determine and describe the strict liability of corporations in environmental law enforcement. The research method used is a normative juridical approach and is descriptive analytical in nature. The data used in this research is secondary data, which is obtained through literature study and analyzed to obtain qualitative data. The conclusion of this study is that strict liability is an accountability without an element of error, where the element of error does not need to be proven by the plaintiff as a basis for compensation payments. The perpetrator or polluter has sufficiently been declared responsible for pollution or environmental destruction, even though the perpetrator has not been found guilty. The concept of strict liability is indirectly an embodiment of legal protection for society, which is the part that has the potential to be harmed as a result of industrial activities carried out. Strict liability arrangements by corporations are stated in Article 88 of Act No. 32 Of 2009. The amount of compensation that can be imposed on environmental polluters or destroyers can be determined to a certain extent.